Menelusuri Kerentanan Kolusi dalam Sistem Peradilan Militer (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The military judiciary, as regulated by law, has the authority to handle military criminal cases and general criminal cases committed by military personnel or persons deemed equivalent to military personnel according to the law. However, its closed and hierarchical nature creates the potential for criminal practices within the military justice system, such as conflicts of interest that could lead to new legal violations in the form of collusion. Therefore, a study is needed to analyse how vulnerable the military justice system is to collusion and the urgency of transparency and reform of the military justice system in order to formulate concrete and sustainable legal reform measures. This research uses a legal-normative approach with qualitative methods. The results of this study show that the military justice system comprises three important elements or bodies, namely Ankum, the Military Prosecutor, and the Military Judge. However, all three are part of the military (TNI) and are therefore subject to military hierarchy, which has the potential to cause conflicts of interest that can lead to new legal violations such as collusion and weaken the objectivity of the legal process, exacerbated by corps solidarity. Collusion practices have many negative impacts, especially when involving the public as victims. Given that the Military Court Act (HAPMIL) has not undergone changes in its legislation, there is a need for transparency and reform of the military court system that aligns with current legal standards.